Natural sources of flavourings : report No. 2 (Council of Europe Publishing, 2007)
This is the second of reports and provides safety-in-use evaluation of 60 source materials.
Keywords: zemědělství a potravinářství; Food Additives; Flavoring Agents; chuťové esence; potravinářské přísady